2017
DOI: 10.3892/ol.2017.5836
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of plasmids into gastric cancer cells by endoscopic ultrasound

Abstract: Abstract. Short hairpin RNA of frizzled-2 (shRNA-Fz2) suppresses the cell proliferation of gastric cancer cells. Endoscopic ultrasound (EUS) is considered a suitable method for the introduction of therapeutic plasmids into cells, since the device enables the access and real-time monitoring of gastric cancer tissues. In the present study, plasmids were introduced into cells by sonoporation, as evidenced by the production of H 2 O 2 . The production of H 2 O 2 was measured by absorbance of a potassium-starch sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Whilst c-myc drives metabolism and proliferation, Hhex appears do the opposite, causing decreased c-Myc activity and reduced tumour growth in a murine xenograft model of HCC (131). However, another study found that Hhex was nevertheless expressed in the majority of HCC cell lines (132).…”
Section: Role Of Hhex In Solid Cancersmentioning
confidence: 99%
“…Whilst c-myc drives metabolism and proliferation, Hhex appears do the opposite, causing decreased c-Myc activity and reduced tumour growth in a murine xenograft model of HCC (131). However, another study found that Hhex was nevertheless expressed in the majority of HCC cell lines (132).…”
Section: Role Of Hhex In Solid Cancersmentioning
confidence: 99%